Dobletes etimológicos en fraseología / Etymological doublets in phraseology - Oksana Gorelova (Ogigia, 2010)
RESUMEN: El artículo analiza un grupo de frases proverbiales españolas que proceden de un mismo étimo latino pero que entraron en la lengua española por dos vías diferentes: la escrita y la hablada, lo que permite llegar a la conclusión de que en el sistema fraseológico español existen dobletes etimológicos.ABSTRACT: The article analyses a group of Spanish proverbial sayings that originate in the same Latin etymon but entered the Spanish language though two two different routes - the written one and the spoken one. This allows us draw conclusions about the existence of etymological doublets in the Spanish phraseological system.